The Management and Imaging of Vestibular Schwannomas - Lin, E.P.; Crane, B.T. (American Journal of Neuroradiology, 2017)
SUMMARY: Vestibular schwannomas are the most common cerebellopontine angle tumor. During the past century, the management goals of vestibular schwannomas have shifted from total resection to functional preservation. Current treatment options include surgical resection, stereotactic radiosurgery, and observation. Imaging has become a crucial part of the initial screening, evaluation, and follow-up assessment of vestibular schwannomas. Recognizing and understanding the management objectives, various treatment modalities, expected posttreatment findings, and complications allows the radiologist to play an essential role in a multidisciplinary team by providing key findings relevant to treatment planning and outcome assessment. The authors provide a comprehensive discussion of the surgical management, role of radiation therapy and observation, imaging differential, and pre- and posttreatment imaging findings of vestibular schwannomas.AAO-HNSAmerican Academy of Otolaryngology-Head and Neck SurgeryCNcranial nerveCPAcerebellopontine angle3D SS-GREvolumetrically acquired steady-state gradient-echoIACinternal auditory canalMFmiddle fossa craniotomyPFposterior fossaRSretrosigmoid craniotomySRSstereotactic radiosurgeryTLtranslabyrinthine craniotomyVSvestibular schwannoma